A case of sporadic erythromelalgia presenting with small fibre neuropathy. Issue 10 (9th October 2019) - Patel, Pavan; Zhang, Yan; Unikel, Lynne H; Edwards, Christopher
Abstract : Erythromelalgia (EM) is a rare disorder of small nerve fibres that leads to painful flushing and burning paresthesisas of the distal extremities and is typically associated with heat or physical activity; relief is found using cooling measures. Its effects are often debilitating in the general population, but this patient had an excellent response to specific treatment options and continues to maintain employment, something many individuals suffering from EM are unable to do. His presentation was also unique in that he had isolated, proximal involvement as his condition progressed whereas typically only the distal extremities are affected. Routine electromyography and nerve conduction studies were normal, whereas nerve biopsy demonstrated findings of small fibre neuropathy. Ultimately, his condition was managed with carbamazepine and his symptoms have almost entirely resolved to date.